Clinical Profile and Outcome of Adult Patients with Scrub Typhus in a Tertiary Care Centre of Eastern Nepal - Ghimire, Ram Hari (JNMA J Nepal Med Assoc, 2020)
INTRODUCTION: Scrub typhus is an under-diagnosed and undertreated zoonotic human infection. There are no data related to profile of adult patients in Nepal. We conducted this study to report socio-demographic, clinical profile and complications of scrub typhus in our scenario. METHODS: This was a descriptive cross-sectional study carried out in Nobel Medical College Teaching Hospital, eastern Nepal. The sample enrollment process was consecutively who were admitted under medical ward and intensive care unit. Diagnosis was established serologically with positive test of IgM antibodies against scrub typhus using immuno-chromatography. Operational definitions for organ system dysfunction were based upon simple available clinic laboratory profiles and imaging. Collected data were entered in Microsoft Excel 2007 and converted it into Statistical Package for Social Science 11.5 Version for statistical analysis. RESULTS: A total of 47 patients were analyzed during this study. Diagnosis of scrub typhus was more common 17 (36.17%) in age group of (40-60 years) with female predominance 32 (68.08%). Most patients (70.15%) were of above 40 years. Fever 47 (100%), asthenia 40 (85.10%), generalized body-ache 41 (87.23%), anorexia 46 (97.87%) and headache 39 (82.97%) were present in most of our patients at sometime during their illness. Respiratory dysfunction was the commonest 37 (78.72%) system dysfunction followed by renal 30 (63.82%) and hepatic 20 (42.55%) impairment. Fortunately no deaths occurred. CONCLUSIONS: Scrub typhus occurred more commonly in elderly female patients. Early empirical treatment may prevent mortality. Large studies involving whole country is needed to see real scenario of disease in this setting.